Use of Dipyridile Amine Functionalized Magnetic Nanoparticles for Preconcentration and Determination of Lead Ions in Food Samples. (27th November 2019) - Karimi, Mohammad; Aboufazeli, Forouzan; Lotfi Zadeh Zhad, Hamid Reza; Sadeghi, Omid; Najafi, Ezzatollah
Abstract: Novel dipyridile-modified Fe3 O4 nanoparticles were synthesized and characterized by infrared spectroscopy, thermal gravimetric and differential thermal analysis, elemental analysis, high-angle X-ray powder diffraction, and scanning electron microscopy. A novel nano-sorbent was used for rapid extraction, preconcentration and determination of trace amounts of lead(II) ions by flame atomic absorption spectrometry. Various adsorption and desorption parameters were optimized during this study. The optimum conditions were pH 6.0; time of adsorption and desorption at 2 and 5 min, respectively; and a maximum capacity value of 192.6 ± 0.7 mg/g (0.93 mmol/g). The RSD and LOD of the method were 1.43% and 0.7 ng/mL, respectively. The LOQ was 2.4 ng/mL. Standard reference materials of National Institute of Standards and Technology (NIST) 1572 and NIST 1571 were used to verify the accuracy of this method. The sorbent allowed for the successful extraction and determination of low levels of Pb(II) ions in various samples of rice, baking powder, wheat, and other foodstuffs.